Association of schizotypy with striatocortical functional connectivity and its asymmetry in healthy adults. Issue 1 (11th October 2017) - Wang, Yi; Ettinger, Ulrich; Meindl, Thomas; Chan, Raymond C. K.
Abstract: Altered striatocortical functional connectivity has been suggested to be a trait marker of schizophrenia spectrum disorders, including schizotypal personality. In the present study, we examined the association between schizotypal personality traits and striatocortical functional connectivity in a sample of healthy adults. The German version of the Schizotypal Personality Questionnaire was obtained from N  = 111 participants recruited from the general public. Resting‐state functional magnetic resonance imaging scans were acquired at 3T. Six striatal seed regions in each hemisphere were defined and striatocortical resting‐state functional connectivity (rsFC) as well as its lateralization indices was calculated. Regression analysis showed that schizotypy scores, especially from the positive dimension, were positively correlated with rsFC between ventral striatum and frontal cortex and negatively associated with rsFC between dorsal striatum and posterior cingulate. No significant associations were found between negative dimension schizotypy and striatocortical rsFC. We also found positive correlations between schizotypy total scores and lateralization index of right dorsal caudate and right rostral putamen. In conclusion, the present study extends previous evidence of altered striatocortical rsFC in the schizophrenia spectrum. The observed associations resemble in part the alterations observed in psychotic patients and their relatives, providing support for dimensionality from schizotypal personality to the clinical disorder. Hum Brain Mapp 39:288–299, 2018 . ©2017 Wiley Periodicals, Inc.